New Wave-Ice Interaction Physics in WAVEWATCH III - Rogers, W E; Zieger, Stefan (2014)
The third generation model for wind-generated surface gravity waves WAVEWATCH III is modified to represent the effect of ice on waves as a source function. This replaces the existing approach of representing ice via fractional blocking (per grid cell) of wave propagation using ice concentration. We have implemented three alternative formulations of varying complexity. The first dissipative source function is a simplistic model where dissipation rate is specified directly. The second dissipative source function, based on work by A. Liu and others, assumes that dissipation is primarily caused by turbulence at the interface between water and a locally continuous ice layer. The third dissipative source function, based on work by H. Shen and others, treats the ice as a locally continuous visco-elastic layer (i.e. a two-layer model). In all cases, the ice characteristics may be specified as non-homogeneous and nonstationary fields. In the latter two source functions, the dissipation rate is non-uniform in frequency space, which is a highly intuitive and documented feature of wave-ice interaction: shorter waves are damped rapidly within the Marginal Ice Zone (MIZ), while the longest waves can penetrate several kilometers (at least) into the ice pack. These source functions are applied in preliminary hindcasts for August 2012 in the Beaufort and Chukchi Seas. Prepared in collaboration with Swinburne University, Melbourne, Australia. For presentation at the IAHR International Symposium on Ice (22nd), Singapore, 11-15 August 2014. The original document contains color images.